Carbon stock in different ecological types of mangroves in a karstic region (Yucatan, México): an opportunity to avoid site scale emissions - Cinco-Castro, Siuling; Herrera-Silveira, Jorge; Montero Muñoz, Jorge Luis; Hernández-Nuñez, Hector; Teutli Hernández, Claudia (Frontiers in Forests and Global Change, 2023)
Mangroves are coastal ecosystems recognized by their capacity to store organic carbon, even more so than tropical and temperate forests. Therefore, they contribute to the local adaptation and mitigation of climate change. Mangroves have different characteristics that origin mangrove ecological types. There are few studies on mangroves in karstic environments, where there is spatial heterogeneity associated with topography-hydroperiod-nutrient interactions. To estimate the total carbon stock in mangroves and determine whether carbon storage differs according to the mangrove ecological type in a natural protected area in the karstic region of the Yucatan Peninsula (northern Ria Celestun Biosphere Reserve), a study was conducted following the recommendations of the IPCC Good Practice Supplement for wetlands and standardized methods used in mangroves studies around the world. According to the results, mangroves associated with springs, called "petenes" or hammock mangroves, showed higher total ecosystem carbon stock (683.7 Mg C ha–1) than fringe, basin, and dwarf mangrove ecological types (429, 385, and 214 Mg C ha-1, respectively). Above- and below-ground carbon stock was different between mangrove ecological types. Carbon stock variation was related to environmental hydrology variables (flooding level, interstitial water salinity, and redox potential). According to the δ13C analysis from the surface soil, carbon accumulated in mangrove sediments in a karstic scenario is mainly autochthonous and predominantly originates from mangrove leaves. Carbon stock in mangroves in the northern Ria Celestun Biosphere Reserve was 9.7 Tg C, of which 40.7% comes from dwarf mangroves due to their extension. These results could be used as a tool for developing specific management actions at regional or local scales for mangrove restoration and conservation.